Strengthening effects of bone marrow mononuclear cells with intensive atorvastatin in acute myocardial infarction - Jun Zhang; Hong Wang; Yuan Wu; Yue-Jin Yang; Hai-Yan Qian; Lei Song; Yong-Jian Geng; Run-lin Gao; Xia-Qiu Tian; Ji Huang; Pei-Sen Huang; Jun Xu; et al. (Open Heart, 2020)
Objective To test whether intensive atorvastatin (ATV) increases the efficacy of transplantation with autologous bone marrow mononuclear cells (MNCs) in patients suffering from anterior ST-elevated myocardial infarction (STEMI).Methods This clinical trial was under a 2×2 factorial design, enrolling 100 STEMI patients, randomly into four groups of regular (RA) or intensive ATV (IA) with MNCs or placebo. The primary endpoint was the change of left ventricular ejection fraction (LVEF) at 1-year follow-up from baseline, primarily assessed by MRI. The secondary endpoints included other parameters of cardiac function, remodelling and regeneration determined by MRI, echocardiography, positron emission tomography (PET) and biomarkers.Results All the STEMI patients with transplantation of MNCs showed significantly increased LVEF change values than those with placebo (p=0.01) with only in the IA+MNCs patients group demonstrating significantly elevation of LVEF than in the IA+placebo group (+12.6% (95%CI 10.4 to 19.3) vs +5.0% (95%CI 4.0 to 10.0), p=0.001), pointing to a better synergy between ATV and MNCs (p=0.019). PET analysis revealed significantly increased viable areas of myocardium (p=0.015), while the scar sizes (p=0.026) and blood aminoterminal pro-B-type natriuretic peptide (p<0.034) reduced. All these above benefits of MNCs were also attributed to IA+MNCs instead of RA+MNCs group of patients with STEMI.Conclusions Intensive ATV treatment augments the therapeutic efficacy of MNCs in patients with anterior STEMI at the convalescent stage. The treatment with the protocol of intensive ATV and MNC combination offers a clinically essential approach for myocardial infarction.Trial registration number NCT00979758.